Event-related and readiness potentials when preparing to approach and avoid alcohol cues following cue avoidance training in heavy drinkers - Lisa C. G. Di Lemma; Andrej Stancak; Vicente Soto; Nick Fallon; Matt Field (Psychopharmacology, 2020)
Rationale Cue avoidance training (CAT) reduces alcohol consumption in the laboratory. However, the neural mechanisms that underlie the effects of this intervention are poorly understood. Objectives The present study investigated the effects of a single session of CAT on event-related and readiness potentials during preparation of approach and avoidance movements to alcohol cues. Methods Heavy drinking young adults ( N = 60) were randomly assigned to complete either CAT or control training. After training, we recorded participants’ event-related and motor readiness potentials as they were preparing to respond. Results In the CAT group, N200 amplitude was higher when preparing to approach rather than avoid alcohol pictures. In the control group, N200 amplitudes did not differ for approach and avoidance to alcohol pictures. Regarding the late positive potential (LPP), in the CAT group, the negativity of this was blunted when preparing to avoid alcohol pictures relative to when preparing to avoid control pictures. In the control group, the negativity of the LPP was blunted when preparing to approach alcohol pictures relative to when preparing to approach control pictures. There were no effects on motor readiness potentials. Behavioural effects indicated short-lived effects of training on reaction times during the training block that did not persist when participants were given time to prepare their motor response before executing it during the EEG testing block. Conclusions After a single session of CAT, the enhanced N200 when approaching alcohol cues may indicate the engagement of executive control to overcome the associations learned during training. These findings clarify the neural mechanisms that may underlie the effects of CAT on drinking behaviour.

Monitoring age‐related trends in genomic diversity of Australian lungfish - Daniel J. Schmidt; Stewart Fallon; David T. Roberts; Thomas Espinoza; Andrew McDougall; Steven G. Brooks; Peter K. Kind; Nick R. Bond; Mark J. Kennard; Jane M. Hughes (Molecular Ecology, 2018)
An important challenge for conservation science is to detect declines in intraspecific diversity so that management action can be guided towards populations or species at risk. The lifespan of Australian lungfish ( Neoceratodus forsteri ) exceeds 80 years, and human impacts on breeding habitat over the last half century may have impeded recruitment, leaving populations dominated by old postreproductive individuals, potentially resulting in a small and declining breeding population. Here, we conduct a “single‐sample” evaluation of genetic erosion within contemporary populations of the Australian lungfish. Genetic erosion is a temporal decline in intraspecific diversity due to factors such as reduced population size and inbreeding. We examined whether young individuals showed signs of reduced genetic diversity and/or inbreeding using a novel bomb radiocarbon dating method to age lungfish nonlethally, based on 14 C ratios of scales. A total of 15,201 single nucleotide polymorphic ( SNP ) loci were genotyped in 92 individuals ranging in age from 2 to 77 years old. Standardized individual heterozygosity and individual inbreeding coefficients varied widely within and between riverine populations, but neither was associated with age, so perceived problems with recruitment have not translated into genetic erosion that could be considered a proximate threat to lungfish populations. Conservation concern has surrounded Australian lungfish for over a century. However, our results suggest that long‐lived threatened species can maintain stable levels of intraspecific variability when sufficient reproductive opportunities exist over the course of a long lifespan.

Abrupt late Pleistocene ecological and climate change on Tahiti (French Polynesia) - Matthew Prebble; Rose Whitau; Jean‐Yves Meyer; Llewellyn Sibley‐Punnett; Stewart Fallon; Nick Porch (Journal of Biogeography, 2016)
Aim To reconstruct ecological changes from the fossil record of a unique wetland on the tropical oceanic island of Tahiti, between 44.5 and 38 cal. kyr bp . Location Vaifanaura'amo'ora, Tamanu Plateau, Punaru'u Valley, Tahiti, Society Islands, French Polynesia (17°38′S, 149°32′50″E). Methods Fossil pollen, spores, seeds, diatoms and invertebrates were examined from a 3.7 m core consisting of Pleistocene‐aged algal sediment overlain by late Holocene peat. Results Between 44.5 and 41.5 cal. kyr bp , Ficus trees, sub‐shrubs including Sigesbeckia orientalis L., the C 4 grass species Paspalum vaginatum Sw., and extinct Pritchardia palms dominated the Vaifanaura'amo'ora wetland. This vegetation association is no longer present in the tropical oceanic Pacific islands. After 41.5 cal. kyr bp, the climate rapidly became drier and cooler with grasses, sedges and ferns dominating the vegetation. Algal sediment accumulation ceased after 38 cal. kyr bp due to prolonged dry climate conditions recorded across the Pacific Ocean. Sediment accumulation recommenced in the late Holocene. Main conclusions The ecological responses identified from Tahiti provide evidence counter to the prevailing view that the tropical oceans buffered the ecological effects of abrupt climate changes during the last glacial period.

Geostatistical Simulation of Acoustic Log Data for Seismic Depth Conversion - Vanessa Cerqueira Koppe; João Felipe Coimbra Leite Costa; Jair Carlos Koppe; Fernando Gambin; Gary Fallon; Nick Davies (Natural Resources Research, 2007)